2014
DOI: 10.3109/02770903.2013.876650
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess inhaler technique and its potential impact on asthma control in patients attending an asthma clinic

Abstract: This study demonstrates the importance of educating and formally assessing inhaler technique in patients with asthma as a part of their ongoing clinical review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 23 publications
2
41
1
Order By: Relevance
“…In previous studies, it has been shown that patients make significant errors when using inhaler devices [6,8,9]. Between 12% and 83.7% of patients are reported to use their inhaler devices with poor inhaler technique [1,5,9,10] and reported adherence rates for inhaler use are between 17.4% and 87.2% [11][12][13]. Inappropriate inhaler technique causes inability to control asthma symptoms, increases in morbidity and mortality, repeated references to hospital, increased cost of treatment and decrease in quality of life [2][3][4][5].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…In previous studies, it has been shown that patients make significant errors when using inhaler devices [6,8,9]. Between 12% and 83.7% of patients are reported to use their inhaler devices with poor inhaler technique [1,5,9,10] and reported adherence rates for inhaler use are between 17.4% and 87.2% [11][12][13]. Inappropriate inhaler technique causes inability to control asthma symptoms, increases in morbidity and mortality, repeated references to hospital, increased cost of treatment and decrease in quality of life [2][3][4][5].…”
Section: Introductionmentioning
confidence: 97%
“…Inhaled drugs play an important role in the treatment of asthma. These drugs are usually in the forms of metered dose inhalers (MDIs) and dry powder inhalers (DPIs) [1]. Despite effective medications and evidence-based guidelines for treatment, many patients with asthma often suffer from exacerbations and persistent symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the relationship between inhaler technique and disease outcomes is further supported by complementary evidence, which shows that by improving inhaler technique improvements in disease outcome can be achieved [8][9][10][11]. For me, the current research of MOLIMARD et al [1] is a disappointing reminder that inhaler technique remains a big problem and a reaffirmation that it really does matter.…”
mentioning
confidence: 97%
“…41 Electronic reminder systems show promise in the case of unintentional non-adherence due to forgetfulness, but seem unlikely to be effective in those intentionally non-adherent and as yet there is no robust evidence relating to their benefits, in terms of long-term adherence or improvements in clinical outcomes. [46][47][48] Inhaler technique problems are compounded by an everincreasing array of inhalers, 49,50 with evidence that health professionals can be as confused as patients. 50 Checking inhaler technique is an essential part of any review.…”
Section: -40mentioning
confidence: 99%